2022
DOI: 10.3390/molecules27082516
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Endo-β-1,4-Xylanase from Streptomyces sp. T7 and Its Application in Xylo-Oligosaccharide Production

Abstract: A xylanase-producing strain, identified as Streptomyces sp. T7, was isolated from soil by our lab. The endo-β-1,4-xylanase (xynST7) gene was found in the genome sequence of strain T7, which was cloned and expressed in Escherichia coli. XynST7 belonged to the glycoside hydrolase family 10, with a molecular mass of approximately 47 kDa. The optimum pH and temperature of XynST7 were pH 6.0 and 60 °C, respectively, and it showed wide pH and temperature adaptability and stability, retaining more than half of its en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…At high incubation temperatures and long incubation times, the yield of reducing sugars was enhanced (Figure 7b). Li et al [36] reported a Streptomyces spp. T7 which was used to produce XOSs from corncob xylan at 60 • C, with the highest yield of reducing sugars.…”
Section: Effect Of the Recombinant Xt6 Xylanase On Reducing Sugar Yie...mentioning
confidence: 99%
“…At high incubation temperatures and long incubation times, the yield of reducing sugars was enhanced (Figure 7b). Li et al [36] reported a Streptomyces spp. T7 which was used to produce XOSs from corncob xylan at 60 • C, with the highest yield of reducing sugars.…”
Section: Effect Of the Recombinant Xt6 Xylanase On Reducing Sugar Yie...mentioning
confidence: 99%
“…Streptomyces sp. produce xylanases, which are utilized in the pulp and paper industry [90,91] and are also able to break down various agricultural residues such as straw waste and oil cake, resulting in enhanced biogas production [91,92] . The industrial application of certain Streptomyces strains that produce xylanase is presented in Table 4.…”
Section: Xylanasesmentioning
confidence: 99%
“… [18b,32a] Endo‐1,4‐ β ‐d‐xylanase is mainly the internal bond of hydrolyzed xylan. Huang et al [54] . isolated a strain of Streptomyces from laboratory soil, which showed that Streptomyces could express endo‐ β ‐1,4‐xylanase.…”
Section: Enzyme Catalysis For Lignocellulose Degradationmentioning
confidence: 99%
“…[18b,32a] Endo-1,4-β-d-xylanase is mainly the internal bond of hydrolyzed xylan. Huang et al [54] isolated a strain of Streptomyces from laboratory soil, which showed that Streptomyces could express endo-β-1,4-xylanase. The results showed that the activity of this enzyme was only endo-β-1, 4-xylanase, not cellulase and β-xylosidase, and the hydrolysis rate of corncob was the highest.…”
Section: Hemicellulasementioning
confidence: 99%